PENERAPAN MODEL INQUIRY LEARNING PADA PEMBELAJARAN IPA SISWA KELAS V DI SD NEGERI 1 SURULANGUN - Handika, Yuyun; Egok, Asep Sukenda; Krisnawati, Yuni (Primary Education Journal Silampari (PEJS), 2024)
This study aims to determine the completeness of science learning outcomes of fifth grade students of SD Negeri 1 Surulangun after the Inquiry Learning learning model is applied. The method used in this study is an experiment with a pre-test and post-test design. The research instrument is in the form of 10 essay questions that have been tested for validity. The sample was taken from a population consisting of only one class, namely class V, with a total of 22 students, making it a saturated sample. The data analysis technique used is descriptive statistical analysis and hypothesis testing to determine the significance of learning outcomes. Based on the results of the hypothesis test, the Zcount value of 6.90 was obtained, which is greater than the Ztable of 1.64 at a significance level of 0.05, so Ho was rejected and Ha was accepted. The results of the study showed that there was a significant completeness of students' science learning outcomes after the application of the Inquiry Learning learning model. This finding confirms that the Inquiry Learning learning model has a significant positive impact on student learning outcomes in science subjects in fifth grade of SD Negeri 1 Surulangun. With these significant results, the Inquiry Learning learning model can be considered an effective method to improve the quality of learning and student achievement. Keywords: Learning outcomes, Inquiry Learning, and Science